The - Ellet, William (Harvard Business Review Press, 2018)
In The Case Study Handbook, Revised Edition, William Ellet presents a potent new approach for efficiently analyzing, discussing, and writing about cases. Early chapters show how to classify cases according to the analytical task they require (making a decision, performing an evaluation, or diagnosing a problem) and quickly establish a base of knowledge about a case. Strategies and templates, in addition to several sample Harvard Business School cases, help you apply the author's framework. Later in the book, Ellet shows how to write persuasive case-analytical essays based on the process laid out earlier. Examples of effective writing further reinforce the methods. The book also includes a chapter on how to talk about cases more effectively in class. Any current or prospective MBA or executive education student needs this guide